Evaluating Two-Photon Absorption Effects on Pulsed High-Power Laser Operation - Piprek, Joachim; Li, Z. M. (2018 International Conference on Numerical Simulation of Optoelectronic Devices (NUSOD), 2018)
The influence of two-photon absorption (2PA) on the pulse power saturation of GaAs-based lasers is investigated and compared to other loss mechanisms. Our numerical model self-consistently solves the drift-diffusion equations and the waveguide equations for a broad-area Fabry-Perot laser diode. Using common absorption parameters, we find that 2PA makes a much smaller contribution to the power saturation than free-carrier absorption (FCA). FCA is mainly caused by carrier leakage from the quantum wells while 2PA-generated carriers are of minor importance.